European vs. American hours worked: assessing the role of the extensive and intensive margins - François Langot; Coralia Quintero-Rojas (Institute for the Study of Labor (IZA), 2008)
Europeans have worked less than Americans since the 1970s. In this paper, we quantify the relative importance of the extensive and intensive margins of aggregate hours of market work on the observed differences. Our counterfactual exercises show that the two dimensions of the extensive margin, the employment rate and the participation rate, explain the most of the total-hours-gap between regions. Moreover, both ratios have similar weight. Conversely, the intensive margin, measured by the number of hours worked per employee, has the smallest role.
urn:nbn:de:101:1-2008120259
Keywords: E2; 330; Hours of market work; participation; employment; intensive and extensive margins; Arbeitszeit; Erwerbstätigkeit; Arbeitslosigkeit; Lohnsteuer; Arbeitsmarktstatistik; Europa; USA